THE IMPACT OF ONLINE DATING ADDICTION ON INTERPERSONAL RELATIONSHIPS AND LIFE SATISFACTION - Jeremy Liasta; Kusumajanti; Witanti Prihatiningsih (SOSIOEDUKASI, 2026)
Dating is an activity carried out by two or more people to get to know each other. In today's modern era, dating can be done online which can lead to addiction. Online dating addiction has become an increasingly common phenomenon among dating app users. This study aims to explore the impact of this addiction on interpersonal relationships and individual life satisfaction. Using qualitative analysis methods, this study collected data from interviews with several informants who are currently actively using the Online Dating application. The results show that online dating addiction can result in a decrease in the quality of interpersonal relationships and reduce life satisfaction, especially among young individuals. These findings are expected to provide insight for app developers and mental health professionals in understanding and addressing problems that arise from this addiction.